Maternal Burnout: Cultural Contribution to The Role of Mothers in Indonesia - Ria Novianti; Ainama Nafisa Putri; Farah Nurhaliza; Srinahyanti (Universitas Pendidikan Ganesha, 2025)
Maternal burnout has become a growing concern as mothers face increasing pressures in caregiving roles. High social expectations often trigger physical, emotional, and psychological exhaustion, which may reduce parenting quality and affect child development. This study aims to analyze the levels and contributing factors of maternal burnout among mothers with young children. The study employed a quantitative approach using a survey design. The participants consisted of 338 mothers from diverse ethnic backgrounds, occupations, and marital statuses. Data were collected through an online questionnaire using the Parental Burnout Assessment (PBA) instrument, which includes four dimensions: exhaustion, contrast with previous parental self, feelings of being fed up with parenting, and emotional distancing from children. The data were analyzed using descriptive statistical analysis to identify patterns of burnout experienced by the participants. The findings indicate that many mothers experience varying levels of burnout in their caregiving roles, particularly in the dimensions of emotional exhaustion and contrast with their previous parental self. Factors such as employment status, number of children, social support from partners or family members, and cultural expectations contribute to the level of burnout experienced. The study concludes that strengthening social support systems and promoting a more balanced distribution of caregiving responsibilities within families are essential for reducing the risk of maternal burnout. These findings imply the importance of increasing family and societal awareness of mothers’ psychological well-being in supporting effective parenting and healthy child development.